Affordance theory can help understanding of individuals' use of online support communities - Coulson, Neil S. (Wiley, 2017)
In the early days of the Internet limited interaction existed between websites and individual users and as a result individuals were largely confined to searching for and reading health-related information. Searching for health-related information remains commonplace (i.e. in 2016, 51% searched for health information online in the UK, ONS, 2016). In addition, more recent technological advances have created forms of electronic communication which have encouraged participation, collaboration and information sharing between users (often referred to as ‘Web 2.0’). One specific way in which this ability to interact with other users has manifest itself is through the development of online support communities (also known as ‘online support groups’). Online support communities are a type of virtual community with a health-related focus, which provide an online environment where individuals can interact with other people who share common interests, experiences or concerns.